ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA SD DALAM MEMECAHKAN MASALAH MATEMATIKA OPEN-ENDED DITINJAU DARI TINGKAT KEMAMPUAN MATEMATIKA - Elly's Mersina Mursidik; Nur Samsiyah; Hendra Erik Rudyanto (IKIP PGRI MADIUN, 2014)
The purpose of this study was to describe the ability to think creatively in elementary grade students in open-ended mathematics problems. The approach used in this study is a qualitative approach that seeks to analyze creative thinking ability of students in open-ended mathematics problems. The subjects were students of class V SDN Kawedanan 2, Kawedanan, Magetan. The subjects were 6 students consisting of two students in high category, 2 students in medium category, and 2 students in low category. Data collection techniques were used are observation, tests and interviews. Data analysis was performed with data reduction, data presentation and verification or conclusion. Technique authenticity of data is done by triangulation of data sources. The results show the good ability of creative thinking of students in higher category and medium category in solving open-endedmathematics problems. Creative thinking ability of students in lower category is the lack of good criteria. Overall for low ability students still need guidance.